Homelessness and housing problems in admitted psychiatric patients in Flanders, Belgium - Catthoor, Kirsten; Van den Broeck, Kris; Hage, Mathilde; Van Suetendael, Luna; Wuyts, Yves; Van Isterdael, Geert; De Hert, Marc (Frontiers in Public Health, 2024)
Homelessness in psychiatric patients in Flanders, Belgium, has never been investigated. Advocacy groups from patients with lived experience of psychiatric disorders have sounded the alarm on the scarcity of suitable housing options, the strain on psychiatric institutions, and the challenges faced by social service workers. To investigate the extent of the problem a survey on the topic was initiated. A "homelessness-in-mental-health-questionnaire" was designed by experts in the field. The social services of all Flemish psychiatric hospitals and all psychiatric wards in general hospitals were contacted and invited to complete this survey. 24 of 70 contacted services responded. The total number of homeless patients in the inpatient setting on an annual basis are estimated to an average 19,5%. 18% of homeless patients remain longer in admission due to the lack of housing options. 13,7% of homeless psychiatric patients are referred to a community care facility such as an assisted living facility. Social service respondents reported spending an average of 27,4% of their work time on housing issues. The main focus points according to the respondents are the lack of priority measures for homeless psychiatric patients, psychiatric problems as a barrier to housing options and the shortage of adapted housing capacity. The conclusion of this study is the need for comprehensive policy interventions to ensure an adequate supply of suitable social housing for psychiatric patients, accessible mental health care, alternative housing options and crisis accommodation facilities. We propose a 10-point action plan on housing for psychiatric patients for policymakers and politicians.